Aplikasi Mobile Berbasis Geolocation untuk Monitoring Harga dan Stok Liquefied Petroleum Gas - Hanan Alif Musthofa; Rodhiyah Mardhiyah (Jutisi : Jurnal Ilmiah Teknik Informatika dan Sistem Informasi, 2025)
The distribution and monitoring of Liquefied Petroleum Gas (LPG) prices in Indonesia is often hampered by limited access to accurate information on prices and stock availability at the retail level. The absence of an integrated information system makes it difficult for the public to access data transparently, which has a negative impact on the smoothness of the supply chain and the effectiveness of monitoring, especially when there are fluctuations in supply. This study aims to develop a geolocation-based mobile application to facilitate the public, shop owners, and agents in monitoring LPG prices and availability directly based on location. The system development applies the Waterfall method, which includes needs analysis, system design using use case diagrams, implementation, and functional testing. Based on the results of black box testing and user trials, the application has been proven to function well in integrating maps to display retailer locations and provide accurate data. It is concluded that this system has successfully fulfilled the research objectives and has significant potential to support information transparency and the digitization of LPG distribution management.Keyword: Geolocation; LPG; Price Monitoring; Transparency; Mobile Application AbstrakDistribusi dan pengawasan harga Liquefied Petroleum Gas (LPG) di Indonesia seringkali terkendala oleh keterbatasan informasi yang akurat mengenai harga dan ketersediaan stok di tingkat pengecer. Absennya sistem informasi terintegrasi menyulitkan masyarakat mengakses data secara transparan, yang berdampak negatif pada kelancaran rantai pasok dan efektivitas pengawasan, khususnya saat terjadi fluktuasi pasokan. Penelitian ini bertujuan mengembangkan aplikasi mobile berbasis geolocation untuk memfasilitasi masyarakat, pemilik toko, dan agen dalam memantau harga serta ketersediaan LPG secara langsung berdasarkan lokasi. Pengembangan sistem menerapkan metode Waterfall yang meliputi analisis kebutuhan, perancangan sistem menggunakan use case diagram, implementasi, hingga pengujian fungsional. Berdasarkan hasil pengujian black box dan uji coba pengguna, aplikasi terbukti berfungsi baik dalam mengintegrasikan peta untuk menampilkan lokasi pengecer serta menyediakan data akurat. Disimpulkan bahwa sistem ini berhasil memenuhi tujuan penelitian dan berpotensi signifikan mendukung keterbukaan informasi serta digitalisasi tata kelola distribusi LPG.